Pendekatan Teori Konstruktivistik dalam Pembelajaran - Aprillia Putri D. H; Muhammad Zakki Fuad; Sinta Dwi Ismaya; M. Yunus Abu Bakar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Abstract. This study aims to examine constructivist theory in depth and its implications for the learning process. Constructivist theory holds that knowledge is not transferred directly from teacher to student but is actively constructed through experience, social interaction, and individual reflection. This study discusses the basic concepts of constructivism, key figures such as Jean Piaget, Lev Vygotsky, John Dewey, and Jerome Bruner, as well as various types of constructivism, including cognitive, social, radical, and humanistic constructivism. Furthermore, this study also examines constructivist learning approaches, such as discovery learning, problem-based learning, project-based learning, cooperative learning, and contextual learning. The method used is library research, analyzing various relevant scientific sources. The results of the study indicate that the constructivist approach can increase student engagement, develop critical thinking skills, and make learning more meaningful because it is oriented towards real-life experiences. Therefore, the application of constructivist theory is highly relevant in supporting student-centered learning. Keywords: Constructivist; learning; Theory; Figure Abstrak. Penelitian ini bertujuan untuk mengkaji secara mendalam teori konstruktivistik serta implikasinya dalam proses pembelajaran. Teori konstruktivistik memandang bahwa pengetahuan tidak ditransfer secara langsung dari guru kepada peserta didik, melainkan dibangun secara aktif melalui pengalaman, interaksi sosial, dan refleksi individu. Kajian ini membahas konsep dasar konstruktivisme, tokoh-tokoh utama seperti Jean Piaget, Lev Vygotsky, John Dewey, dan Jerome Bruner, serta berbagai jenis konstruktivisme seperti konstruktivisme kognitif, sosial, radikal, dan humanistik. Selain itu, penelitian ini juga mengulas pendekatan pembelajaran konstruktivistik seperti discovery learning, problem-based learning, project-based learning, cooperative learning, dan contextual learning. Metode yang digunakan adalah studi kepustakaan (library research) dengan menganalisis berbagai sumber ilmiah yang relevan. Hasil kajian menunjukkan bahwa pendekatan konstruktivistik mampu meningkatkan keaktifan siswa, mengembangkan keterampilan berpikir kritis, serta menjadikan pembelajaran lebih bermakna karena berorientasi pada pengalaman nyata. Oleh karena itu, penerapan teori konstruktivistik sangat relevan dalam mendukung pembelajaran yang berpusat pada siswa. Kata kunci: Konstruktivistik; pembelajaran; teori; tokoh